PENDAMPINGAN LITERASI PADA ANAK MELALUI MEDIA PAPAN KATA DI SDK KEKAJODHO - Maria Trisanti Woga; Konstantinus Dua Dhiu; Yasinta Maria Fono (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This service is entitled Literacy Assistance for children through word board media at SDK Kekajodho. The purpose of this service is to introduce the concept of words to children to improve literacy through word board media. The methods used methods used are observation, interview, and documentation. The results of the this assistance shows that this media assistance carried out by Teaching Campus students is able to improve students' literacy Teaching Campus students are able to improve students' literacy. Interview results interview results also show that using word board media is very effective for children because it is a direct teaching tool that can be displayed or used by students. children because it is a direct teaching aid that can be shown or shown to children and can be shown to children and can help children recognise words and improve literacy. Word boards can also can improve children's ability to recognise and distinguish letters.